Molecular dynamics study on the reinforcing effect of incorporation of graphene/carbon nanotubes on the mechanical properties of swelling rubber. (October 2021) - Yang, Bin; Wang, Shijie; Song, Zhaobo; Liu, Lingfeng; Li, Hualei; Li, Yunlong
Abstract: Molecular models of the swollen nitrile rubber (NBR) matrix reinforced by the same weight percentage of the carbon nanotubes (CNT) and graphene (GN) were developed. The tensile and shear behaviors of the composites in swollen state were mainly studied via molecular dynamics simulations. The simulation results showed that the introduction of CNT and GN significantly improved the mechanical properties of the swollen NBR matrix. Higher elastic modulus, tensile strength and shear modulus of the composites were obtained by the incorporation of GN as reinforcement than that of CNT. With the increase in CNT/GN content, the elastic modulus, tensile strength and shear modulus of the swollen NBR matrix were further improved. It was also observed that CNT/GN prevented the diffusion of the cyclohexane and delayed the swelling of the NBR matrix, and GN performed better. To explore the mechanisms on the above phenomenon, the atom displacements, interaction energy between the nano-reinforcements and rubber matrices, MSD of the cyclohexane and the free volume of the polymer composites were examined and interpreted accordingly. Highlights: Molecular models of the swollen NBR matrix reinforced by CNT/GN are developed for the first time via MD method. The introduction of CNT/GN significantly improves the mechanical properties of the swollen NBR matrix. GN is proven to enhance better mechanical properties of the NBR matrix than CNT. Visualize the displacement of atoms during stretching and shearing process.